Recurrent tibial intra-cortical osteosarcoma: A case report and review of the literature - Olarn Arpornchayanon (2018)
Introduction. Intra-cortical osteosarcoma is the rarest subtype of osseous-producing tumor. Most reported cases present a low-grade histology with slow progression and good oncological control after adequate treatment. In this report, we describe a case and review the literature to propose adequate treatment. Case presentation. We present the case of a 21-year-old Thai woman who was thought to have an intra-cortical osteosarcoma of the right tibia. We performed a wide resection and reconstruction with bone transportation using an Ilizarov external fixator. The tumor recurred five years later at the same site with a similar histology. We performed a new resection and reconstruction by ankle arthrodesis with adjuvant chemotherapy. At the last follow-up, she had remained active and free from disease for seven years. Conclusion: This case report of recurrent intra-cortical osteosarcoma describes an atypical presentation. The low-grade histology, adequate surgical margin and adjuvant chemotherapy of the recurrent lesion were favorable factors, and our patient has remained free of any tumor recurrence. © 2011 Arpornchayanon et al; licensee BioMed Central Ltd.